Peran Dinas Perindustrian dan Perdagangan Provinsi Jawa Barat Melalui Program Pasamoan dalam Mendukung Pemasaran Produk UMKM - Rosmiah Sabirah; Herry Sutanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of the West Java Provincial Department of Industry and Trade through the PASAMOAN (Pasar Minggon Industri dan Perdagangan) Program in supporting the marketing of micro, small, and medium enterprises (MSMEs) products. The study was motivated by limited market access, inadequate promotional activities, and low brand awareness of regional flagship products. A qualitative descriptive approach was employed by collecting data through direct observation during an internship program, supported by documentation of institutional records and official publications. The findings indicate that the PASAMOAN Program serves as an effective promotional platform that expands market access, enhances product exposure and brand awareness, strengthens business networks, and fosters collaboration among government, business actors, and the community. The program also contributes to trade stabilization by providing affordable basic necessities to the public. These findings demonstrate that PASAMOAN is an effective government-facilitated marketing initiative for improving the competitiveness and sustainability of MSME product marketing in West Java Province.